2012
DOI: 10.1155/2012/543537
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinical Outcomes of Flexible Ureterorenoscopy with Holmium Laser for Renal Stone Greater than 2 cm

Abstract: Objective. To evaluate the clinical outcome of flexible ureterorenoscopy (F-URS) with holmium laser in managing renal stone greater than 2 cm. Patients and Methods. Records of 120 patients (123 renal units) with renal stone greater than 2 cm who underwent F-URS with holmium laser iwere evaluated. The mean stone size was 26.3 mm. Patient and stone characteristics, perioperative outcomes and complications were evaluated. The outcome was determined at 4 weeks on plain radiograph (KUB) and Non-contrast CT scan (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…These studies did not focus on URSL or large stones and were therefore excluded. Seventeen further papers were excluded upon reading the full manuscript, leaving 12 papers [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies did not focus on URSL or large stones and were therefore excluded. Seventeen further papers were excluded upon reading the full manuscript, leaving 12 papers [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The age range was 18-86 years. Five of the studies were from the USA [9][10][11][12][13]16], the rest were individually from France [7], UK [8], Japan [12], India [14], Poland [15], Egypt [17] and Germany [18]. The included studies range from 1998-2013.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…In recent years, more and more doctors have been able to skillfully operate the flexible ureteroscope and determine the efficacy of ureteroscopy as an alternative to PCNL to tackle large renal stones. RIRS had an average stone-free rate of around 91-97.5% for stones >2 cm, with an average number of procedures of no more than two [5,30,31,32,33,34,35]. Takazawa et al [6] reported that in kidney stones 2-4 cm in size, after three procedures the stone-free rate was up to 100% with no major intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, with the advances in flexible ureteroscopic instrumentation and holmium laser lithotripsy, retrograde intrarenal surgery (RIRS) has become an increasingly considered option for intrarenal stone removal. Some studies [5,6] reported a stone-free rate near to 92% in patients with large stones. RIRS has been widely accepted in the management of larger renal stones as an alternative to PCNL.…”
Section: Introductionmentioning
confidence: 99%
“…They included only patients who had a ureteral J-stent inserted preoperatively. Al-Qahtani et al [21] reported renal pelvis perforation in 1 of 120 patients. Minimal mucosal erosions or mucosal tears can be managed conservatively without inserting a ureteral J-stent (grade 1), but severe mucosal injuries as for example ureteral perforation are mostly treated by placing a ureteral J-stent (grade 2) successfully.…”
Section: Discussionmentioning
confidence: 99%